Future Developments and Applications of the Vaccines against Dangerous Viral Infections, RNA-Replicon-Based, Obtained from the Venezuelan Equine Encephalomyelitis Virus - A. A. Petrov; V. N. Lebedev; T. M. Plekhanova; L. F. Stobva; O. N. Sidorova; E. V. Mel’Nikova; S. V. Borisevich (Проблемы особо опасных инфекций, 2014)
The members of the Filoviridae (Marburg and Ebola viruses) and Arenaviridae (Lassa, Lujo, Machupo, Junin, Guanarito, Sabia viruses) families are the etiological agents of particularly dangerous viral hemorrhagic fevers. These agents pose a potential threat to public health care in view of the possibility of their unintended import into the non-endemic regions, and thus construction of specific medical protectors as regards induced by them diseases is a pressing issue. According to leading experts, vaccination of the cohorts that fall in the risk groups is the most effective and least expensive method to prevent the development of epidemics. The review contains information on a new prospective line of protective preparations development as regards particularly dangerous viral infections - construction of alphavirus-replicon-based vaccine. Elaboration of recombinant replicons does not require cultivation of pathogenic microorganisms. RNA-replicons are distinguished by their incapacity to produce infective progeny, which is of a great importance for the development of vaccines against particularly dangerous viral hemorrhagic fevers. Advantages of alphaviral replicons over other RNA-replicons are as follows: high levels of heterologous gene expression and resistance to anti-vector immunity. RNA-replicons of alphaviruses combine the safety of inactivated, and immunogenicity of live attenuated vaccines. Alphaviruses-based replicons are suitable for express vaccine development with the purpose of specific prophylaxis of viral infectious diseases.